Papiri della Società Italiana. Vol. XVII Volume diciassettesimo (PSI XVII) - Maltomini, Francesca; Russo, Simona; Stroppa, Marco (Edizioni dell'Istituto Papirologico «G. Vitelli», 2018)
This XVII volume of the PSI series includes the edition of 62 texts, all preserved on papyri belonging to the Papyrological Institute «G. Vitelli». Fragments of known authors offer passages from Homer, Herodotus, Xenophon, Demosthenes, Diodorus Siculus, as well as the Acts of the Apostles, Gregory of Nyssa and Basil of Caesarea; some fragments of erudite prose stand out among the masterless texts. The paraliterary texts include, in addition to two astronomical fragments, a lexicon and two Homeric glossaries. There is a wide range of documentary texts, both official and private: reports, requests, contracts, certificates, declarations, accounts, letters.